Gender differences in the presentation and outcomes of hospitalized patients with COVID-19 - Biolé, Carloalberto; Akın, Ibrahim (Journal of hospital medicine, 2021)
*Corresponding Author: Enrico Cerrato, MD, Email: enrico.cerratogmail.com; Telephone: +390119026802; Twitter: @enrico_cerrato.